2012
DOI: 10.1063/1.3689187
|View full text |Cite
|
Sign up to set email alerts
|

Magnetohydrodynamic flow of a binary electrolyte in a concentric annulus

Abstract: We study theoretically magnetohydrodynamic (MHD) motion of a binary electrolyte in a concentric annulus subjected to a uniform, axial magnetic field. The annulus' cylindrical surfaces serve as electrodes. When a potential difference is imposed across the cylindrical electrodes, radial electric current flows in the solution and interacts with the axial magnetic field to induce a Lorentz body force that drives azimuthal fluid flow. When the annulus is infinitely long, a purely azimuthal flow (analogous to the cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 35 publications
0
7
0
2
Order By: Relevance
“…The profiles indicate that the velocity is maximum close to the channel walls, with large velocity gradients near the maxima and small gradients at the center. These M-shaped profiles are typical of magnetohydrodynamically driven flow, [55][56][57][58] and the fast regions near channel walls are caused by strong fringing fields at the magnet edges. The apparatus behaves much as we would expect.…”
Section: Methodsmentioning
confidence: 99%
“…The profiles indicate that the velocity is maximum close to the channel walls, with large velocity gradients near the maxima and small gradients at the center. These M-shaped profiles are typical of magnetohydrodynamically driven flow, [55][56][57][58] and the fast regions near channel walls are caused by strong fringing fields at the magnet edges. The apparatus behaves much as we would expect.…”
Section: Methodsmentioning
confidence: 99%
“…Para la validación teórica del modelado matemático del mezclador MHD propuesto se realizó una investigación de los antecedentes y del estado del arte. La mayoría de los modelados asumían que la profundidad del canal h era infinita y, por lo tanto, la relación de aspecto ε también tendía al infinito (Qin & Bau, 2012). Solo se encontraron los resultados de tres prototipos con la configuración de canal anular abierto (Digilov, 2007;West, 2003;Qin & Bau, 2012), pero de distintas dimen-siones a las propuestas.…”
Section: Validación Teórica Y Experimental Del Mezclador Magnetohidrodinámicounclassified
“…During the research of the state of art, was found that previous experiments have been done where a circular flow of a weakly conducting fluid was induced by a Lorentz force. Nevertheless, most of them assume that cylinders are infinitely long and that viscous friction is not present due to the non-existence of bottom effects [ 19 ].…”
Section: Theoretical Validation Of Mathematical Modelmentioning
confidence: 99%